The Arden research handbook of Shakespeare and textual studies - Erne, Lukas 1968- (<<The>> Arden Shakespeare, 2021)
"The Arden Research Handbook of Shakespeare and Textual Studies is a wide-ranging, authoritative guide to research on Shakespeare and textual studies by an international team of leading scholars. It contains chapters on all the major areas of current research, notably the Shakespeare manuscripts; the printed text and paratext in Shakespeare's early playbooks and poetry books; Shakespeare's place in the early modern book trade; Shakespeare's early readers, users, and collectors; the constitution and evolution of the Shakespeare canon from the sixteenth to the twenty-first century; Shakespeare's editors from the eighteenth to the twenty-first century; and the modern editorial reproduction of Shakespeare. The Handbook also devotes separate chapters to new directions and developments in research in the field, specifically in the areas of digital editing and of authorship attribution methodologies. In addition, the Companion contains various sections that provide non-specialists with practical help: an A-Z of key terms and concepts, a guide to research methods and problems, a chronology of major publications and events, an introduction to resources for study of the field, and a substantial annotated bibliography. The Arden Research Handbook of Shakespeare and Textual Studies is a reference work aimed at advanced undergraduate and graduate students as well as scholars and libraries, a guide to beginning or developing research in the field, an essential companion for all those interested in Shakespeare and textual studies"--
Keywords: Shakespeare, William -- 1564-1616; Textgeschichte; Textkritik; Edition; Shakespeare, William / 1564-1616 / Criticism, Textual; Shakespeare studies & criticism; Electronic books; Aufsatzsammlung